2023
DOI: 10.1186/s12913-023-09083-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental health professionals and telehealth in a rural setting: a cross sectional survey

Abstract: Background Telehealth usage has been promoted in all settings but has been identified as a panacea to issues of access and equity in the rural context. However, uptake and widespread integration of telehealth across all parts of the health system has been slow, with a myriad of barriers documented, including in rural settings. The crisis of the COVID-19 pandemic, saw barriers rapidly overturned with the unprecedented and exponential rise in telehealth usage. The uniqueness of the crisis forced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…The review concluded "Whilst rural and remote youth may prefer to access mental health services in person rather than via telehealth, further well-designed research is needed to better understand under what circumstances this preference holds true and why" [21]. While telehealth has potential to reduce barriers and improve access to healthcare for vulnerable populations, there still remains inequity in telehealth accessibility, for example, those living in rural and remote areas generally have reduced access to reliable technological infrastructure and internet [7,26,27]. Some people may lack the requisite skills or equipment [28,29], and tele-health may be less suitable for some groups.…”
Section: Acceptability and Suitability Of Tele-mental Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…The review concluded "Whilst rural and remote youth may prefer to access mental health services in person rather than via telehealth, further well-designed research is needed to better understand under what circumstances this preference holds true and why" [21]. While telehealth has potential to reduce barriers and improve access to healthcare for vulnerable populations, there still remains inequity in telehealth accessibility, for example, those living in rural and remote areas generally have reduced access to reliable technological infrastructure and internet [7,26,27]. Some people may lack the requisite skills or equipment [28,29], and tele-health may be less suitable for some groups.…”
Section: Acceptability and Suitability Of Tele-mental Healthmentioning
confidence: 99%
“…While telehealth has potential to reduce barriers and improve access to healthcare for vulnerable populations, there still remains inequity in telehealth accessibility, for example, those living in rural and remote areas generally have reduced access to reliable technological infrastructure and internet [ 7 , 26 , 27 ]. Some people may lack the requisite skills or equipment [ 28 , 29 ], and tele-health may be less suitable for some groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Programs like the Sarva Shiksha Abhiyan (SSA) aim to promote inclusive education, though the implementation is often inconsistent in rural areas [8]. Teletherapy and mobile health (mHealth) solutions are emerging as viable alternatives to traditional therapy, providing continuous support and access to specialized services in remote locations [9,10].…”
Section: Neurodevelopmentalmentioning
confidence: 99%
“…Teletherapy and mobile health (mHealth) solutions have emerged as viable alternatives to traditional therapy services. These technologies can connect individuals in rural areas with specialists and provide continuous support through remote monitoring and intervention [9,10].…”
Section: Behavioral and Therapeutic Interventionsmentioning
confidence: 99%